2021
DOI: 10.1111/sdi.12958
|View full text |Cite
|
Sign up to set email alerts
|

Absolute blood volume variations during hemodialysis: Does dialysate temperature play a role?

Abstract: Background: Vascular refilling occurs to preserve hemodynamic stability during hemodialysis (HD). Recent studies report a feasible and noninvasive method to determine absolute blood volume (ABV), and estimate vascular refilling during HD. The objective of this study is to analyze if lowering dialysate temperature modifies variations in ABV during HD. Methods:The study was performed in 50 patients under HD. During two different sessions, relative blood volume was assessed using dialysate temperatures of 35.5°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Recently, we developed a method to determine absolute blood volume during routine HD sessions 11,12 . This offered the possibility to quantify vascular refilling in different clinical settings 10,13–15 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a method to determine absolute blood volume during routine HD sessions 11,12 . This offered the possibility to quantify vascular refilling in different clinical settings 10,13–15 …”
Section: Introductionmentioning
confidence: 99%
“…In previous clinical studies on vascular refilling, the refilling fractions reached a mean level of about 70-75% with relatively large individual variability (SD about ± 10%, or even individually minimum 40 and maximum 98%). 4,6,10,11,[13][14][15][16][17][18][19] In theory, the sum of refilling fraction and BV/ECV ratio should be 1. 11 However, we could not confirm this hypothesis in this study (sum 1.07).…”
Section: Discussionmentioning
confidence: 99%
“…30 A recently published study has also shown that, in a selected group of patients, the use of cool dialysate (35.5 C) may reduce ABV drop during HD treatments. 31 However, further studies are needed to understand how different hemodialysis parameters modify ABV drop or F ref and minimize IME.…”
Section: Discussion/conclusionmentioning
confidence: 99%